The impact of out-of-home care on brain development: a brief review of the neuroscientific evidence informing our understanding of children’s attachment outcomes - Oliveira, Paula S. (Frontiers in Behavioral Neuroscience, 2024)
Researchers interested in the effects of early experiences of caregiving adversity have employed neuroscientific methods to illuminate whether and how such environmental input impacts on brain development, and whether and how such impacts underpin poor socioemotional outcomes in this population. Evidence is compelling in documenting negative effects on the individual's neurodevelopment following exposure to adverse or disadvantaged environments such as institutionalisation or maltreatment. Neuroimaging research focused specifically on attachment-relevant processing of socioemotional stimuli and attachment outcomes amongst children looked-after is scarcer, but largely consistent. This review begins by summarising the key general brain structural and functional alterations associated with caregiving deprivation. Then, neuroscientific evidence that is more directly relevant for understanding these children's attachment outcomes, both by employing social stimuli and by correlating children's neural markers with their attachment profiles, is reviewed. Brief interpretations of findings are suggested, and key limitations and gaps in the literature identified.